Going west : adapted from the Little house books by Laura Ingalls Wilder - Wilder, Laura Ingalls, 1867-1957; Graef, Renee (My first Little house books., 1996)
A young pioneer girl and her family prepare to leave the big woods of Wisconsin and travel west in their covered wagon.